The diagnostic challenge of orbital tuberculosis in an otherwise healthy individual: A case report - Kartiwa, Raden Angga; Elsyanty, Firda Muthia; Setiawan, Grace; Dewi, Niluh Putu Ayu; Boesoirie, Shanti Fitrianti; Dahlan, Mohammad Rinaldi (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Ocular tuberculosis occurs in 1.5-18% of all extrapulmonary tuberculosis cases, with orbital tuberculosis being a very small proportion of all cases of ocular tuberculosis. High variability of manifestations of orbital tuberculosis may result in delayed diagnosis. Children are the populations most affected by this disease. This study aims to report a case of orbital tuberculosis in a patient without systemic tuberculosis symptoms. We presents a 13-year-old girl who is reported protrusion of the right eye for four months. She complained diplopia and pain in the right eye radiating to the head. She reported no other systemic symptoms. Ophthalmological examination revealed that her best corrected visual acuity of the right eye was 0.25, and the left eye was 1.0. The movement of the right eye was limited to the superior, temporal, and nasal directions. Anterior segment examinations demonstrated proptosis of the right eye with 3 mm of lagophthalmos. The patient then underwent an orbitotomy and biopsy procedure. Histopathological analysis revealed chronic granulomatous inflammation with Langerhans cells, indicative of tuberculosis. The patient was diagnosed with proptosis of the right eye and multiple cranial nerve palsy due to orbital tuberculosis. The patient was subsequently prescribed an antituberculosis treatment and attended regular monthly follow-ups. Ten months after surgery and completed antituberculosis treatment, the proptosis improves and there is no further growth of the mass. Orbital tuberculosis is a rare condition and is often challenging to diagnose, particularly in healthy individuals. Thorough history taking, physical examination, and ancillary testing are essential to establish an accurate diagnosis. This case emphasizes the necessity for heightened suspicion of tuberculosis in atypical presentations, particularly in pediatric patients in endemic areas, to prevent morbidity and ensure timely treatment.